Haikyu!! 3-in-1 edition. 10-11-12 - Furudate, Haruichi, 1983- (Shonen Jump manga., 2025)
"Hinata boldly declares that he won't close his eyes for the Freak Quick anymore, but Kageyama isn't having any of it. The two of them fight, setting the entire team back in the practice game. But after coming face-to-face with how polished the Tokyo teams are, Karasuno realizes that even with extra practice, the road to new skills and a better-prepared team is still long. Looking for new ways to fight in the air, Hinata goes to Fukurodani's ace, Kotaro Bokuto, for some help"--Back cover.